The Islamic Law Perspective toward Implementation of Post-Divorce Women’s Rights - Millah, Widatul; Huda, Miftakhul (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
Women's rights after divorce in the provision of iddah maintenance are regulated in Marriage Law No. 1 of 1974 and the Compilation of Islamic Law. The provision of iddah maintenance is divided into two parts, related to the divorce process, namely divorce raj' and divorce bain. In the case of raj’i divorce, the provision of iddah maintenance is clearly regulated that a woman who is divorced raj’i gets the right to iddah maintenance because raj’i divorce causes a wife to have a waiting period before they enter into the next marriage. Meanwhile, iddah maintenance in bain divorce is not regulated in the Compilation of Islamic Law or the Law. This confirms that women who are divorced bain do not get iddah maintenance. However, these provisions contain interpretations and are clarified by several relevant provisions such as PERMA No. 3 of 2017. This paper uses a normative juridical approach, which focuses on the applicable laws and regulations related to post-divorce iddah maintenance with a submission from the woman or post-divorce bain sughra. This study found that first, the provisions regarding iddah alimony whose submission process is carried out by women, contain generality. However, the generality is clarified or specialized by PERMA No. 3 of 2017 in relation to several other provisions, which explain the ex officio rights of a judge. Secondly, the laws and regulations related to iddah alimony that are listed have not yet been fully implemented.